EARNINGS MANAGEMENT DI INDONESIA: SEBUAH STUDI LITERATUR - Celine Alexandra; Margaretha Lionardi; Sanchian Jennefer; William Lim; Carmel Meiden (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2022)
This study describes the evolution of earnings management research in Indonesia taken from journals studied in Indonesia and indexed with sinta 1-3 with the research year 2018-2021. The purpose of research is to add and develop research or articles on earnings management contained in journals in Indonesia. The sample was obtained as many as 23 articles. The research categorizes articles based on research years, research variables, research analysis methods, research theory, research types, research sectors, and research models contained in the articles. The research method used is a systematic literature review. From this literary study, we can conclude that research related to earnings management have decreased in the year 2021, the commonly used variable is leverage, the research method mostly used is multiple linear regression, generally used theory is agency theory, type of earnings management study normally used is quantitative, manufacture sector is often used research sector, and modified jones model by DeChow et al. is commonly used for measuring earnings management.